Influence of environmental factors on the presence of Vibrio cholerae in the marine environment: a climate link - Violeta Trinidad Pardío Sedas (Journal of Infection in Developing Countries)
Evidence indicates that the atmospheric and oceanic processes that occur in response to increased greenhouse gases in the broad-scale climate system may already be changing the ecology of infectious diseases. Recent studies have shown that climate also influences the abundance and ecology of pathogens, and the links between pathogens and changing ocean conditions, including human diseases such as cholera. Vibrio cholerae is well recognized as being responsible for significant mortality and economic loss in developing countries, most often centered in tropical areas of the world. Within the marine environment, V. cholerae is found attached to surfaces provided by plants, filamentous green algae, copepods, crustaceans, and insects. The specific environmental changes that amplified plankton and associated bacterial proliferation and govern the location and timing of plankton blooms have been elucidated. Several studies have demonstrated that environmental non-O1 and non-O139 V. cholerae strains and V. cholerae O1 El Tor and O139 are able to form a three-dimensional biofilm on surfaces which provides a microenvironment, facilitating environmental persistence within natural aquatic habitats during interepidemic periods. Revealing the influence of climatic/environmental factors in seasonal patterns is critical to understanding temporal variability of cholera at longer time scales to improve disease forecasting. From an applied perspective, clarifying the mechanisms that link seasonal environmental changes to diseases’ dynamics will aid in developing strategies for controlling diseases across a range of human and natural systems.